The strength of long-distance ties for aging healthy with HIV: the case of rural South Africa - Yu, Shao-Tzu; Houle, Brian; Kabudula, Chodziwadziwa W; Bärnighausen, Till; Gómez-Olivé, F Xavier; Angotti, Nicole (The journals of gerontology. Series B, Psychological sciences, social sciences, 2025)
Objectives: In lower-income settings with limited government-funded care, personal social networks are often the primary means by which older persons access resources and support. We tested the association between long-distance ties—ties that span greater geographical and network distances—and HIV treatment outcomes in a rural South African community with one of the largest aging populations with HIV.